2017
DOI: 10.1371/journal.pone.0170635
|View full text |Cite|
|
Sign up to set email alerts
|

Risk factors associated with sexually transmitted infections among HIV infected men who have sex with men

Abstract: To investigate the factors associated with sexually transmitted infection and Human Immunodeficiency Virus (STI-HIV) co-infection among men who have sex with men (MSM). A total of 357 HIV-infected participants (84 STI-HIV co-infection and 273 HIV infections only) were recruited from Jiangsu, China. Logistic regression analyses were used to estimate the related factors associated with STI-HIV co-infection. Marginal structural models were adopted to estimate the effect of transmission drug resistance (TDR) on ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In the present study, a rather high STI prevalence among HIVpositive individuals was con rmed, namely, 47.0% (191/406) in total,45.1% (91/204) in ART-naive individuals and 49.0% (99/202) in ART individuals. This prevalence is much higher than the 5.3% observed in the HIVpositive individuals in Nepal [19], the 11.1% detected in the women living with HIV/AIDS (WLHA) in Uganda [20] and the 23.5% of HIV-infected MSM in China [21], but the prevalence was less than the 60.6% of female sex workers in Peru [22] and the 60.5% of HIV-infected Women in Zimbabwe [23]. The prevalence of genital tract discomfort was 0.5%…”
Section: Discussionmentioning
confidence: 69%
“…In the present study, a rather high STI prevalence among HIVpositive individuals was con rmed, namely, 47.0% (191/406) in total,45.1% (91/204) in ART-naive individuals and 49.0% (99/202) in ART individuals. This prevalence is much higher than the 5.3% observed in the HIVpositive individuals in Nepal [19], the 11.1% detected in the women living with HIV/AIDS (WLHA) in Uganda [20] and the 23.5% of HIV-infected MSM in China [21], but the prevalence was less than the 60.6% of female sex workers in Peru [22] and the 60.5% of HIV-infected Women in Zimbabwe [23]. The prevalence of genital tract discomfort was 0.5%…”
Section: Discussionmentioning
confidence: 69%
“…In the present study, a rather high STI prevalence among HIV-positive individuals was confirmed, namely, 47.0% (191/406) in total, 45.1% (91/204) in ART-naive individuals and 49.0% (99/202) in individuals receiving ART. This prevalence is much higher than the observed prevalence of 5.3% in HIV-positive individuals in Nepal [ 19 ], 11.1% in women living with HIV/AIDS (WLHA) in Uganda [ 20 ] and 23.5% in HIV-infected men who have sex with men (MSM) in China [ 21 ], but the prevalence was less than that of 60.6% in female sex workers in Peru [ 22 ] and 60.5% in HIV-infected women in Zimbabwe [ 23 ]. The prevalence of genital tract discomfort was 0.5% (2/406), which was lower than the STI prevalence.…”
Section: Discussionmentioning
confidence: 94%
“…Opportunistic screening for other STIs during medical visits for anogenital warts helps doctors identify common yet asymptomatic co-infecting diseases that would have otherwise been overlooked and under-reported by patients. While opportunistic screening is oftentimes applied for patients from high-risk groups, [21][22][23][24][25][26][27][28][29]33,34 expanding this procedure for men and women newly diagnosed with anogenital warts can improve treatment and care for patients in China. This approach enables Chinese doctors to follow international protocols of screening non-high-risk populations consistent with other low-and-middle 8,37 as well as highincome 5,9,31,36 countries.…”
Section: Resultsmentioning
confidence: 99%
“…Much of the available clinical research from China is based on studies of high-risk groups such as FSWs, 26,27 MSM, 22,24,25 HIV-positive patients, 29 and migrants, 28 and only on a limited range of common STI co-infections. In reviewing research conducted in China from data collected between 1998 and 2017 on STI co-infections, we find that the majority of studies target MSM, FSWs, HIV-positive, and HIV high-risk populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation